Gender dimensions of decision-making on production assets and challenges facing women. Issue 1 (2nd January 2016) - Quaye, Wilhelmina; Dowuona, Solomon; Okai, Mary; Dziedzoave, Nanam
ABSTRACT: This article investigates gender dimensions of decision-making on access to, and control over, productive assets for agricultural development in selected communities in Ghana. The men were more educated, resourced, and economically empowered than the women. This resulted in differential access to, and control over, resources by gender and a low level of female participation in decision-making. The study identified a land access gap by gender and crop acreage gap of up to 80% for women as compared to men. Challenges limiting women in agricultural production and processing include inadequate land access, inadequate capital, inefficient processing technologies, and unattractive markets.